"Like Mother, Like Daughter?" Perspectives on Mother to Daughter Succession in Diasporic Culinary Fiction by Women - R.L.A. Nipuni Ranaweera (The Open University of Sri Lanka, 2022)
This work is based on the role migrant women have played in history as preservers of culture especially through the culinary domain. Then shifted the focus to fictional representations of migrant women. Popular culinary fictions by migrant women writers typically highlight the cooking mother 'from home' as a symbol for continuing traditions and for nostalgic reminiscences of nurturing. This study attempts to look beyond this familiar paradigm and to explore the significance of these mother figures in new and insightful ways which draw attention to their cooking as a powerful motif as well as their ability to influence the way in which their daughters navigate their diasporic existence. This work analyzes mother-daughter bonds represented in the fictions of two writers, namely Chitra Bannerjee Divakaruni and Amulya Malladi and then studird how the 'traits of these fictional mothers are 'carried forward' by their daughters highlighting the way in which the mothers' skills often undergo a process of transformation in their daughters' hands. This type of lineage or succession which resonates with the idea of a matrilineal traditions expounded by feminist theorists can be further complicated by the associations with queer diasporas and global capitalism.